Incidence of Poverty in Nepal from 1995/96 to 2022/23 - Kumar, Nand Kishor; Khanal, Tantrika Raj (Cognition, 2026)
Poverty is the absence of or deprivation of basic commodities and services. The fundamental amenities that the impoverished need to survive and lead regular lives—such as food, clothing, shelter, education, and health care—are denied to them. Poverty is a multifaceted issue that has its roots in social and cultural standards at the local level. It is defined as the denial of material, bodily, and social requirements. The inability to provide for basic necessities such as clothing, food, housing, basic medical care, education, and other forms of physical well-being is what is known as poverty. In Nepal, poverty is a pervasive condition. The patterns, inequalities, and variance of poverty in Nepal are presented in this article. According to this report, Nepal has been gradually but steadily lowering poverty for a considerable amount of time. Between 1995/96 and 2022/23 Nepal made measurable progress in reducing monetary poverty, but the pace and pattern varied across time, space, and by how poverty was measured. Using the four rounds of the Nepal Living Standards Survey (NLSS I IV), the national headcount of consumption poverty fell from about 41.8% in 1995/96 to 30.9% in 2003/04, 25.2% in 2010/11, and 20.3% in 2022/23. These headline numbers mask important measurement changes, urban–rural differences, and interruptions caused by shocks (notably the 2015 earthquake and the COVID-19 era).